Phase Behavior and Capillary Condensation Hysteresis of Carbon Dioxide in Mesopores - Dantas, Silvio; Struckhoff, Katie Cychosz; Thommes, Matthias; Neimark, Alexander V. (Langmuir, 2019)
Carbon dioxide adsorption on micro- and mesoporous carbonaceous materials in a wide range of temperatures and pressures is of great importance for the problems of gas separations, greenhouse gas capture and sequestration, enhanced hydrocarbon recovery from shales and coals, as well as for the characterization of nanoporous materials using CO2 as a molecular probe. We investigate the influence of temperature on CO2 adsorption focusing on the capillary condensation and hysteresis phenomena. We present experimental data on the adsorption of CO2 on CMK-3, ordered carbon with mesopores of ∼5-6 nm, at various temperatures (185-273 K) and pressures (up to 35 bars). Using Monte Carlo (MC) simulations in the grand canonical and mesocanonical ensembles, we attempt to predict the transition from reversible capillary condensation to hysteretic adsorption-desorption cycles that is experimentally observed with the decrease of temperature. We show that although the desorption at all temperatures occurs at the conditions of pore vapor-liquid equilibrium, the capillary condensation is a nucleation-driven process associated with an effective energy barrier of ∼43 kT, specific to the sample used in this work. This barrier can be overcome at the equilibrium conditions in the region of reversible condensation at temperatures higher than 240 K. At lower temperatures, the regime of developing hysteresis is observed with progressively widening hysteresis loops. The position of capillary condensation transition is estimated using the pressure dependence of the energy barrier calculated by the thermodynamic integration of the van der Waals-type continuous canonical isotherm simulated with the gauge cell MC method. These findings lay the foundation for developing kernels of CO2 adsorption and desorption isotherm for calculating the pore size distribution in the entire range of micropore and mesopore sizes from one high-pressure experimental isotherm.
CRIS-Team Scopus Importer:2019-09-17